Sn = (3/2) n² - (1/2)n
S2 = (3/2).2² - (1/2).2 = 6 - 1 = 5
S1 = (3/2).1²- (1/2).1 = 3/2 - 1/2 = 1
U1 = S1 = 1
U2 = S2 - S1 = 5 - 1 = 4
beda = 4 - 1 = 3
Un = a + (n-1).b
Un = 1 + (n-1).3
Un = 1 + 3n - 3
Un = 3n -2
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Sn = (3/2) n² - (1/2)n
S2 = (3/2).2² - (1/2).2 = 6 - 1 = 5
S1 = (3/2).1²- (1/2).1 = 3/2 - 1/2 = 1
U1 = S1 = 1
U2 = S2 - S1 = 5 - 1 = 4
beda = 4 - 1 = 3
Un = a + (n-1).b
Un = 1 + (n-1).3
Un = 1 + 3n - 3
Un = 3n -2